Illegal Fishing: Analysis of MV Nika Case in International Criminal Law Perspective - Handaruan, Fath Diene Yuslima (International Law Discourse in Southeast Asia, 2024)
Indonesia, the world's largest maritime country, faces significant challenges in protecting its vast marine resources from illegal fishing by foreign vessels, a transnational crime recognized globally since the 2000s. Illegal fishing results in substantial economic losses, estimated at over 100 trillion Indonesian rupiahs annually, and undermines local fisheries, food security, and marine ecosystem sustainability. In response, Indonesia has implemented robust national laws, including Law Number 32 of 2014 concerning Maritime Affairs and Law Number 6 of 2023 concerning Cipta Kerja, which affirm its jurisdiction and impose stringent penalties on violators. Notable cases like the interception of MV Nika, a vessel involved in multiple international violations, highlight the country's commitment to enforcing maritime law. Indonesia collaborates extensively with international entities such as INTERPOL and regional partners through initiatives like the Regional Plan of Action to Combat Illegal, Unreported, and Unregulated Fishing (RPOA-IUU). These efforts aim to enhance maritime surveillance, legal enforcement, and sustainable fisheries management, ensuring the protection of Indonesia's maritime wealth for future generations.